Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3201/eid2504.180691
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations and Molecular Diagnosis of Scrub Typhus and Murine Typhus, Vietnam, 2015–2017

Abstract: Scrub typhus was the predominant rickettsial disease diagnosed among hospitalized patients with acute undifferentiated fever in northern Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 36 publications
2
20
2
3
Order By: Relevance
“…In this study, only 33% of the patients were PCR þ ve. Given the relatively low sensitivity, other studies have demonstrated the value of performing PCR and serology for admission samples [21,22]. This study also examined the immune response following three different antibiotic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only 33% of the patients were PCR þ ve. Given the relatively low sensitivity, other studies have demonstrated the value of performing PCR and serology for admission samples [21,22]. This study also examined the immune response following three different antibiotic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although an antibody detection assay in the form of rapid tests is available and may be utilized as a point-of-care test, these tests are less sensitive during the early phase of the disease and may not be useful for providing information concerning options for early treatment. Besides, more recently, various versions of PCR with sensitivity ranging from 73 to 100% have been developed for scrub typhus early diagnosis [ 17 , 18 , 19 , 20 ]. Nevertheless, PCR is not a point-of-care test, especially for the resource-limited areas where endemic scrub typhus is a local healthcare concern.…”
Section: Introductionmentioning
confidence: 99%
“…After approximately half a century of neglect, scrub typhus is beginning to receive more attention as an important cause of non-malarial febrile illness in Vietnam. Recent reports highlight scrub typhus as a disease of high clinical relevance and expanding (documentation of) distribution due to a notable recent increase in the number of diagnosed and reported cases [ 14 , 15 ]. In the 1960s, scrub typhus was considered a common disease among American veterans in Vietnam and an endemic disease in the midlands and mountainous forests of Vietnam, but after the discovery of Chloramphenicol the general interest in rickettsial diseases declined gradually with the availability of an effective antimicrobial [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam only a limited number of cases were registered after the 1970s, but the increasing reports of scrub typhus in recent years suggest a re-emerging trend of this rickettsial illness with documented geographical expansion and distribution within the population of Vietnam [ 8 , 15 , 18 ]. Results from various causes-of-fever studies in Southeast Asia have confirmed the importance of this easily treatable rickettsial disease [ 9 , 15 , 18 ]. Scrub typhus is a serious disease if untreated in elderly; the median mortality is 6% if untreated, and mortality increases with age (over 50 years old mortality >45%), while case fatality risks can reach 12–13% in South India or North Thailand [ 11 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%